Is there an association between traumatic peripheral lesions and cognitive impairments in adults? A scoping review - Xue Zhang; Tamara Tse; Tianyi Li; Maryam Zoghi (Advances in Rehabilitation, 2023)
The aim of this scoping review was to critically review and synthesize the evidence concerning the relationship between traumatic peripheral lesions and cognitive impairments. Five electronic databases (Medline, Cinahl, Psycinfo, Embase, and Cochrane Library) were searched in their entirety using the two key words “cognition” and “trauma”. An additional manual search was conducted. All inclusion criteria comprised English language, an assessment of cognition, and the study participants experienced acute peripheral lesion or physical trauma and were aged between 18 and 65 years. The articles were screened for eligibility by two independent reviewers. Disagreements were resolved by discussion or consensus with a third author. A total of 11737 records were identified, of which 10 met the inclusion criteria. Whiplash injury, brachial plexus injury, soft tissue injury around the cervical spine, and fracture were found to be associated with cognitive impairments. The earliest cognitive assessment time point was one-month post injury, while the latest counterpart was 444 months. Cognition was assessed using 20 unique instruments, targeting nine distinct cognitive domains. An overall positive association was found between traumatic peripheral lesions and cognitive impairments. Therefore, further longitudinal research is needed to monitor the changes in cognitive functions post physical trauma.